Involvement of calpain in 4-hydroxynonenal-induced disruption of gap junction-mediated intercellular communication among fibrocytes in primary cultures derived from the cochlear spiral ligament - Taro Yamaguchi; Masanori Yoneyama; Eiichi Hinoi; Kiyokazu Ogita (Elsevier, 2015)
The endocochlear potential in the inner ear is essential for hearing ability, and maintained by various K+ transport apparatuses including Na+, K+-ATPase and gap junction-mediated intercellular communication (GJ-IC) in the lateral wall structures of the cochlea. Noise-induced hearing loss is known at least in part due to disruption of GJ-IC resulting from an oxidative stress-induced decrease in connexins (Cxs) level in the lateral wall structures. The purpose of this study was to investigate, using primary cultures of fibrocytes from the cochlear spiral ligament of mice, the mechanism underlying GJ-IC disruption induced by 4-hydroxynonenal (4-HNE), which is formed as a mediator of oxidative stress. An exposure to 4-HNE produced the following events: i.e., an increase in 4-HNE-adducted proteins; a decrease in the protein levels of Cx43, β-catenin, and Cx43/β-catenin complex along with intracellular translocation of this complex from the cell membrane to the cytoplasm; enhanced calpain-dependent degradation of endogenous α-fodrin; and disruption of GJ-IC. The 4-HNE-induced decrease in these protein levels and disruption of GJ-IC were most completely abolished by the calpain inhibitor PD150606. Taken together, our data suggest that 4-HNE disrupted GJ-IC through calpain-mediated degradation of Cx43 and β-catenin in primary cultures of fibrocytes derived from the cochlear spiral ligament.